ANALISIS KONDISI PERKERASAN JALAN MENGGUNAKAN METODE PCI PADA JALAN RAYA SIBANG KAJA, KABUPATEN BADUNG - Wibawa, I Putu Chandra; Ariawan, I Made Agus; Thanaya, I Nyoman Arya; Sariantini, Ni Wayan (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Road pavement condition is an important factor in supporting the safety, comfort, and smoothness of traffic, particularly during high traffic activity and volume, such as on the Sibang Kaja Highway in Badung Regency. As pavement service life increases and traffic load on the road infrastructure increases, various types of pavement damage on the surface begin to appear, potentially reducing the functional performance of the road. This study aims to analyze the pavement condition of Sibang Kaja Highway using the Pavement Condition Index (PCI) method and to provide recommendations for road maintenance management based on the level of damage. The research method used the PCI method through a visual field survey to identify the type, severity, and extent of pavement damage, which were then analyzed to obtain PCI values for each sample unit and road segment. The analysis results show that the dominant types of damage include alligator cracks, block cracks, patches, and raveling, with PCI values across segments ranging from poor to satisfactory. The average PCI value of 56.72 for each segment indicates that the pavement condition is in the fair category, indicating that the pavement is still functional but has experienced a decline in performance. Based on the percentage of damaged area, a combination of routine, periodic, and rehabilitation programs is recommended for specific segments. This research provides a basis for decision-making in prioritizing road maintenance and rehabilitation.